Natriuretic peptides in the control of lipid metabolism and insulin sensitivity. (12th September 2017) - Verboven, K.; Hansen, D.; Jocken, J. W. E.; Blaak, E. E.
Summary: Natriuretic peptides have long been known for their cardiovascular function. However, a growing body of evidence emphasizes the role of natriuretic peptides in human substrate and energy metabolism, thereby connecting the heart with several insulin‐sensitive organs like adipose tissue, skeletal muscle and liver. Obesity may be associated with an impaired regulation of the natriuretic peptide system, also indicated as a natriuretic handicap. Evidence points towards a contribution of this natriuretic handicap to the development of obesity, type 2 diabetes mellitus and cardiometabolic complications, although the causal relationship is not fully understood. Nevertheless, targeting the natriuretic peptide pathway may improve metabolic health in obesity and type 2 diabetes mellitus. This review will focus on current literature regarding the metabolic roles of natriuretic peptides with emphasis on lipid metabolism and insulin sensitivity. Furthermore, it will be discussed how exercise and lifestyle intervention may modulate the natriuretic peptide‐related metabolic effects.